Cervical Cancer Recurrence and Patient Survival After Radical Hysterectomy Followed by Either Adjuvant Chemotherapy or Adjuvant Radiotherapy With Optional Concurrent Chemotherapy: A Systematic Review and Meta-Analysis - Zhang, Yu-fei; Fan, Yu; Zhang, Peng; Ruan, Jia-ying; Mu, Yi; Li, Jin-ke (Frontiers in Oncology, 2022)
Objective To compare cervical cancer recurrence and patient survival after radical hysterectomy followed by either adjuvant chemotherapy (AC) or adjuvant radiotherapy with or without concurrent chemotherapy (AR/CCRT). Methods We systematically searched PubMed, EMBASE, the Cochrane Library and clinicaltrials.gov to identify studies reporting recurrence or survival of cervical cancer patients who received AC or AR/CCRT after radical hysterectomy. Data were meta-analyzed using a random-effects model, and heterogeneity was evaluated using the I2 test. Subgroup and sensitivity analyses were performed to identify potential sources of heterogeneity. Results The meta-analysis included 14 non-randomized studies and two randomized controlled trials, altogether involving 5,052 cervical cancer patients. AC and AR/CCRT groups did not differ significantly in rates of total or local recurrence or mortality. Nevertheless, AC was associated with significantly lower risk of distant recurrence [odds ratio (OR) 0.67, 95% confidence interval (CI) 0.55-0.81] and higher rates of overall survival [hazard ratio (HR) 0.69, 95%CI 0.54-0.85] and disease-free survival rate (HR 0.77, 95%CI 0.62-0.92). Conclusions AC may be an effective alternative to AR/CCRT for cervical cancer patients after radical hysterectomy, especially younger women who wish to preserve their ovaries and protect them from radiation damage. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier PROSPERO (CRD42021252518).